2013
DOI: 10.1039/c3cp53362j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of benzimidazole ethylphosphonate: a solid-state NMR study of anhydrous composite proton-conducting electrolytes

Abstract: Imidazole phosphate and phosphonate solid acids model the hydrogen-bonding networks and dynamics of the anhydrous electrolyte candidate for proton exchange membrane fuel cells. Solid-state NMR reveals that phosphate and phosphonate anion dynamics dominate the rate of long-range proton transport, and that the presence of a membrane host facilitates proton mobility, as evidenced by a decreased correlation time of the composites (80 ± 15 ms) relative to the pristine salt (101 ± 5 ms). Benzimidazole ethylphosphona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…14,28,34,35 For example, proton local mobility has been analyzed by monitoring the 1 H− 1 H dipolar coupling interactions using the 1 H MAS DQ recoupling technique, which has helped to establish proton conducting mechanism in solid acid materials by observing changes in H-bonding network. 34,35 This DQ NMR technique has also been applied to comparing proton conductivity in Nafion and sulfonated poly(ether ether ketone) by probing the change in H-bonding interactions. 28 In the S-PEEK materials, the investigation focused on the proton dynamics and resulting proton conduction mechanism in membrane materials.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,28,34,35 For example, proton local mobility has been analyzed by monitoring the 1 H− 1 H dipolar coupling interactions using the 1 H MAS DQ recoupling technique, which has helped to establish proton conducting mechanism in solid acid materials by observing changes in H-bonding network. 34,35 This DQ NMR technique has also been applied to comparing proton conductivity in Nafion and sulfonated poly(ether ether ketone) by probing the change in H-bonding interactions. 28 In the S-PEEK materials, the investigation focused on the proton dynamics and resulting proton conduction mechanism in membrane materials.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Homonuclear recoupling ssNMR pulse sequences have been applied to understand the structure ,, and local dynamics of small molecules in the solid state. ,,, For example, proton local mobility has been analyzed by monitoring the 1 H– 1 H dipolar coupling interactions using the 1 H MAS DQ recoupling technique, which has helped to establish proton conducting mechanism in solid acid materials by observing changes in H-bonding network. , This DQ NMR technique has also been applied to comparing proton conductivity in Nafion and sulfonated poly­(ether ether ketone) by probing the change in H-bonding interactions . In the S-PEEK materials, the investigation focused on the proton dynamics and resulting proton conduction mechanism in membrane materials.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…11,55 The slow (from 0.1 s −1 to 3000 s −1 ) molecular motions in solid-state electrolytes as well as their structural characterization were investigated by using the center band-only detection of exchange (CODEX) NMR technique. 56 Briey, CODEX is a stimulated-echo experiment under MAS conditions with chemical-shi-anisotropy recoupling and intensity referencing as for rotational-echo, double-resonance (REDOR) NMR. 57 The last one is a high-resolution ssNMR experiment for measuring the dipolar coupling between heteronuclear spin pairs.…”
Section: Hmbcmentioning
confidence: 99%
“…Promising alternatives to Nafion include inorganic and organic solid acids due to their temperature and electrochemical stability. Inorganic solid acids were first introduced by Haile et al using CsHSO 4 , which was shown to provide high proton conductivity for up to 80 h at 250 °C . Solid-acid systems utilize the Grotthuss mechanism for proton conduction instead of the vehicle mechanism, which may enable anhydrous high temperature operating conditions.…”
Section: Introductionmentioning
confidence: 99%